CONTEXTUALIZATION OF HADITH REGARDING THE PROHIBITION OF ANNOUNCING LOSS IN THE MOSQUE (A Study of the Meaning of Hadith) - Fatchur Yunan Bachtiar; Herman Darmawan; Anang Fajar Hasbi; Muhammad Fitri; Muhammad Jikri (Riwayah: Jurnal Studi Hadis, 2025)
As an identity of the Islamic community, the mosque holds a very important role and function. The mosque does not only focus on activities related to the afterlife but integrates both spiritual (ukhrawi) and worldly (duniawi) activities. Regarding the function of the mosque, the Prophet Muhammad (peace be upon him) prohibited the announcement of lost items in the mosque because it was not built for such a purpose. However, this prohibition contrasts with the mosque’s function not only as a place of worship but also as a medium to address social issues within the community. Therefore, this study aims to understand the hadith related to this prohibition by examining its contextualization in the study of Ma’anil Hadith. This research is a library study using qualitative methods, conducted by collecting and analyzing data relevant to the issue being investigated. The results of this study are: First, the hadith prohibiting the announcement of lost items in the mosque signifies that the mosque is a sacred place, with a peaceful and calm atmosphere, where worship activities such as prayer are performed. Second, when contextualized in the present day, there are many ways to search for lost items in the mosque, such as reporting the loss to the mosque administrators, asking the congregation at the mosque doors, looking in the lost and found area outside the mosque, and posting announcements about lost items on the information board outside the mosque.